Pengaruh bahan pengisi serat kaca terhadap sifat fisik dan kristalinitas polipaduan PC/ABS - Dwi Wahini Nurhajati; Muhammad Sholeh; Ihda Novia Indrajati; Ike Setyorini (Majalah Kulit, Karet, dan Plastik, 2017)
This research aimed to determine the effects of the addition of glass fibers on the physical and crystallinity properties of PC/ABS polyblends. The ratio of PC/ABS used in this research was 75/25, while the addition of glass fibers ranged from 0; 5; 10; to 15 phr (based on the weight of PC/ABS). Polyblends of PC/ABS/glass fibers were prepared in a twin screw extruder. The test results showed that density and tensile strength of PC/ABS polyblends increased with an increase in the glass fiber content. The presence of glass fibers decreased MFI and impact strength of these PC/ABS polyblends. The functional groups were determined by the fourier transform infrared (FTIR) spectrophotometer while crystallinity was examined using X-ray diffractometer (XRD).Keywords: PC/ABS polyblend, glass fiber, physical properties, crystallinity.